We are given:
"U = \\{ a, b, c, d, e, f, g, h \\}"
"A = \\{ a, b, c, d \\}"
"B = \\{ c, e, g \\}"
"C = \\{ d, e, f, g, h \\}"
Now:
"B \\cup C = \\{ c,e,g \\} \\cup \\{ d, e, f, g, h \\}"
"\\hspace{1 cm} \\, = \\{ c, d, e, f, g, h \\}"
And:
"B \\cap C = \\{ c,e,g \\} \\cap \\{ d, e, f, g, h \\}"
"\\hspace{1 cm} \\, = \\{ e, g \\}"
a.)
"A \\cup \\left( B \\cap C \\right) = \\{ a,b, c, d \\} \\cup \\{ e, g \\}"
"\\hspace{1 cm}\\hspace{0.9 cm} \\, = \\{ a, b, c, d, e, g \\}"
b.)
"B \\cup C = \\{ c,e,g \\} \\cup \\{ d, e, f, g, h \\}"
"\\hspace{1 cm} \\, = \\{ c, d, e, f, g, h \\}"
c.)
"\\left( B \\cup C \\right)^{'} = U - \\left( B \\cup C \\right)"
"\\hspace{1 cm} \\hspace{0.4 cm} = \\{ a, b, c, d, e, f, g, h \\} - \\{ c, d, e, f, g, h \\}"
"\\hspace{1 cm} \\hspace{0.4 cm} = \\{ a, b \\}"
d.)
"A - \\left( B \\cup C \\right) = \\{ a, b, c, d \\} - \\{ c, d, e, f, g, h \\}"
"\\hspace{1 cm} \\hspace{1 cm} = \\{ a, b \\}"
e.)
"\\left( B \\cup C \\right) - A = \\{ c, d, e, f, g, h \\} - \\{ a, b, c, d \\}"
"\\hspace{1 cm} \\hspace{1 cm} = \\{ e, f, g, h \\}"
Comments
Leave a comment